‘Death livens you up’: death education through the eyes of adolescents - Rodríguez Herrero, Pablo; Serrano Manzano, Bianca Fiorella; de la Herrán Gascón, Agustín (Pedagogy, Culture and Society, 2024)
From a Pedagogy of Death perspective, this study focuses on education for a more conscious life that includes an awareness of death. The objective was to ascertain in depth the views of adolescents on teaching about death in their particular context. The methodology adopted was qualitative and phenomenological. Seven focus groups were organised with high-school students from 12 to 18 years of age from 7 different Spanish schools. Analysis of their views yielded valuable findings: death was interesting to them in the areas of gender violence, health, sustainability and suicide. Participants called for organised guidance from trained educators through which they would be able to discuss this taboo topic, have meaningful encounters with others, create humanising educational environments and raise their individual and collective awareness. The study found that the adolescents were interested in death and in death education; that the creativity and relevance of their observations could produce significant educational knowledge; and that training for educators and their good rapport with students were seen as key to the inclusion of death in a more developed curriculum and for counselling and guidance in situations of bereavement.
Keywords: adolescent; didactics of death; education; focus group; pedagogy of death; Spanish; teaching; Scopus; Emerging